Procedural features of interrogating a juvenile suspected of murder - О. Р. Zavorina (Law and Safety)
The article is devoted to the analysis of procedural features of interrogation of a juvenile who has committed a criminal offense, in particular murder. The procedural order and tactical features of the interrogation of a juvenile, defined in international law, are analyzed. Criteria, certain rules of interrogation, as well as requirements for such procedural action are given. The need for further improvement of national legislation in accordance with international standards in the field of criminal procedural support of pre-trial investigation is identified. Attention is drawn to the lack of a legally regulated procedure for interrogation of juveniles by the Green Room method and the inconsistency of national legislation of Ukraine with the requirements of the Convention on the Rights of the Child (1991) for interrogators of juveniles. To address these inconsistencies, it is proposed to introduce refresher courses for juvenile investigators, interrogators, prosecutors and judges. According to the results of studying the experience of foreign countries, the practice of using structured interrogation protocols in the pre-trial investigation of this category of criminal proceedings was established, namely the international protocol for interviewing children - NICHD, and it is proposed to implement such developments in the practice of juvenile investigators.